The arrogant ape and the wise firefly - Bhunjun, Mirana R. Medina (Manila University of Santo Tomas Pub. House, 2002)
In Palawan, there lives Aylirog, toughest of all the apes. He is large and arrogant and enjoys throwing his weight around. One evening as he is falling asleep, he sees a light coming toward him. It is Alitaptap, a little firefly. Aylirog stops him and tells him he is not allowed to pass through that part of the forest because it belongs to the apes. What does Alitaptap have to do to get through the forest to see his dying mother?
Text in English and Filipino.
"Based on a Visayan folktale."
Title from cover.
"...highly recommended in terms of imaginative handling of figures, color and general design..."
Finalist 1st Philippine Board on Books for Young People (PBBY) illustrators prize 1984.
Keywords: Apes -- Juvenile literature; Fireflies -- Juvenile literature